Development and Testing of a New Simplified Endoscopic Mucosal Assessment for Crohn's Disease: The SEMA-CD. Issue 10 (31st December 2020) - Adler, Jeremy; Eder, Sally J; Gebremariam, Acham; French, Kelley Rose; Moncion, Ila; Singer, Andrew A M; Bass, Lee M; Moran, Christopher J; Picoraro, Joseph A; Moses, Jonathan; Lewis, Jeffery D; Sandberg, Kelly C; et al.
Abstract: Objectives: Endoscopic mucosal improvement is the gold standard for assessing treatment efficacy in clinical trials of Crohn's disease. Current endoscopic indices are not routinely used in clinical practice. The lack of endoscopic information in large clinical registries limits their use for research. A quick, easy, and accurate method is needed for assessing mucosal improvement for clinicians in real-world practice. We developed and tested a novel simplified endoscopic mucosal assessment for Crohn's disease (SEMA-CD). Methods: We developed a 5-point scale for ranking endoscopic severity of ileum and colon based on Simple Endoscopic Score for Crohn's disease (SES-CD). Central readers were trained to perform SES-CD and SEMA-CD. Pediatric patients with Crohn's disease undergoing colonoscopy were enrolled. Video recordings of colonoscopies were de-identified and randomly assigned to blinded central readers. The SES-CD and SEMA-CD were scored for each video. The SES-CD was considered the validated standard for comparison. Correlation was assessed with Spearman rho, inter- and intrarater reliability with kappa statistics. Results: Fifty-seven colonoscopies were read a total of 212 times. Correlation between SEMA-CD and SES-CD was strong (rho = 0.98, P < 0.0001). Inter-rater reliability for SEMA-CD was 0.80, and intrarater reliability was 0.83. Central readers rated SEMA-CD as easier than SES-CD. Conclusion: The SEMA-CD accurately and reproducibly correlates with the standard SES-CD. Central readers viewed SEMA-CD as easier than SES-CD. Use of SEMA-CD in practice should enable collecting mucosal improvement information in large populations of patients. This will improve the quality of research that can be conducted in clinical registries. External validation is needed. Graphical Abstract: